Magnetic resonance of cardiac tumors and masses - Berden, Pavel (Radiology and oncology (Ljubljana), 2000)
Cardiac tumors are rare and should be differentiated from nontumoral cardiac masses because of different therapeutic approach. For this purpose, spin-echo (SE) technique and gradient-echo (GE) technique are used in magnetic resonanceimaging (MR). The first provides anatomic evaluation of the heart andtissue characterization, while the second provides dynamic information on the blood flow and heart contraction. Cardiac myxoma is differential from thrombus by paramagnetic contrast agent administration. Their mobility is evaluated with GE technique. Lipomas and subacute hemorrhage have the same, high signal intensity on T1-weighted spin-echo image, therefore, the fat suppression technique is appropriate to recognize them. MR is used in evaluating the response of the malignant tumor to chemotherapy. GE MR is useful to differentiate between the thrombus and slow-flowing blood; the administration of gadolinium helps to distinguish the thrombus from the tumor.In patients suspected of having a cardiac tumor, echocardiography is thefirst method of choice. MR is used to confirm the findigs of echocardiography, to determine precisely the tumor location, extent, and its tissue characterization, to follow up patients under treatment, and to detect early tumor recurrence.
Keywords: Diagnosis, differential; diagnostika; Echocardiography; Heart neoplasms; Hemorrhage; Lipoma; Magnetic resonance imaging; Myxoma; rak (medicina); Recurrence; slikanje z jedrsko magnetno resonanco; srce; Thrombosis; Treatment outcome